Multiomic analysis reveals that the flavonoid biosynthesis pathway is associated with cold tolerance in Heracleum moellendorffii Hance - Liu, Guan; Gao, Huan; Song, Yu; Wang, Hanhui; Zhang, Dongye; Wang, Yang; Liu, Shuo; Li, Zhonghua; Liu, Changhua; Sun, Yan (Frontiers in Plant Science, 2025)
Heracleum moellendorffii Hance is a perennial herbaceous plant that is adaptable to cold environments and has both edible and medicinal value. Given that no reference genome for this species is available, we constructed a high-quality transcript isoform library using full-length transcriptome sequencing and conducted a comparative genomic analysis. Samples were obtained from plants that had been subjected to cold stress for 12, 24 and 36 hours (Cold_12, Cold_24, and Cold_36, respectively) and from control plants (Cold_0) that were not subjected to cold stress and used in transcriptome and nontargeted metabolome analyses. Compared with the genes expressed in CK (Cold_0), the number of differentially expressed genes (DEGs) in Cold 12, Cold_24, and Cold_36 increased gradually over time; plants subjected to 12, 24 and 36 hours of cold stress displayed 669, 6084, and 24,129 DEGs, respectively. The DEGs were clustered into 8 subclasses by k-means clustering; subclasses 2, 3, 4, and 7 were enriched in pathways related to “flavonoid biosynthesis”. Nontargeted metabolome analysis revealed that 3719 annotated metabolites were shared by all four groups of samples. We identified 1186, 1087, and 1097 differentially accumulated metabolites (DAMs) in three comparisons: Cold_12 vs. CK, Cold_24 vs. CK, and Cold_36 vs. CK, respectively. The DAMs were predominantly enriched in the “flavonoid biosynthesis pathway”. Through WGCNA, we obtained five modules and 29 flavonoid-related metabolites with extremely significant module−metabolite paired relationships (|correlation coefficient|> 0.9, P < 0.01). We analysed the DEGs and DAMs of the flavonoid biosynthetic pathway in H. moellendorffii Hance under cold stress and constructed a correlation network between transcription factors (TFs) and structural genes in the pathway. RT−qPCR was used to confirm the expression of four hub genes from the WGCNA, six TFs, and 15 structural genes of the flavonoid biosynthetic pathway. These data provide a foundation for functional genomics studies of H. moellendorffii Hance and contribute to the study of the molecular mechanisms and transcriptional regulation of flavonoid accumulation by TFs under cold stress conditions in plants.